Choice of assay affects serum albumin measurements in HIV patients: A comparison of bromocresol green and bromocresol purple dye binding methods - Parmar, Amrita; Agarwal, Deeptika; Saha, Tapan; Somani, Babu; Misra, Pratibha (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: Dye-binding assays - bromocresol green (BCG) and bromocresol purple (BCP) -are widely used for serum albumin measurement. Differences between the results reported by these assays can have important clinical implications. There are limited studies elucidating the differences between the results of two assays in HIV patients. We aimed to determine whether the choice of assay affects serum albumin measurements in HIV patients. Materials and Methods: Hundred newly diagnosed HIV patients were included in the study. The subjects were followed up for 6-12 months after initiating ART. Hundred HIV-negative healthy controls matched for age and body mass index were taken as controls. Serum albumin and three acute phase proteins (APPs) (Alpha-1 acid glycoprotein, C-reactive protein, ceruloplasmin) were measured. Serum albumin measurement was done by both BCG and BCP dye binding methods. Paired t-test was used to compare the groups. Results: The concentration of APPs reduces with ART indicating reduced inflammation, and is lowest in the control group. The difference in serum albumin concentrations measured by the two dye binding methods reduces with reduction in APPs. The study further indicates that the BCG method gives higher values of serum albumin as compared to BCP method in the presence of other proteins in the sample. Conclusion: The choice of albumin assay affects the serum albumin assessment of HIV patients. We recommend that the BCP assay be used to measure serum albumin in HIV patients, particularly in patients not on ART.